Medical management versus chemical cautery with medical management in treatment of inferior turbinate hypertrophy: a comparative study - Gosavi, Rahul S.; Shahane, Prateek P.; Magdum, Vishal K.; Gosavi, Shishir D.; Bachhav, Kalpesh S.; Purohit, Gautam S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Patients having inferior turbinate hypertrophy causing intractable sneezing, rhinnorhoea which is non-responsive to conventional medication require alternative therapies. Aim of the study was to compare medical management vs chemical cautery with medical management in treatment of inferior turbinate hypertrophy since both these treatments are easily accessible, cost effective to the patients as well as not associated with major complications. The complaints sneezing, rhinorrhoea, nasal blockage, headache, eye irritation and redness of patients are reduced and quality of life of patients improved after chemical cautery with medical management as compared to medical management alone. 50 patients of age group 15-75 years with c/o Sneezing, rhinorrhoea, nasal blockage and headache were included in our study. Inferior turbinate hypertrophy was diagnosed on the basis of anterior rhinoscopy and diagnostic nasal endoscopy. Patients were divided randomly in 2 group-group A (medical management), group B (chemical cautery with medical management). The 22 question sino-nasal outcome test (SNOTT22) score and rhinomanometry was done before and after treatment to compare the efficacy and detect symptom free period in both groups. Percentage of relief was more among group B patients as compared to group A patients. Symptom free period was more in group B patients as compared to group A patients and both of them were analysed on the basis of SNOTT22 score and rhinomanometry. Chemical cautery with topical application of silver nitrate coupled with medical management is more effective in treatment of inferior turbinate hypertrophy as compared to medical management alone.